2021
DOI: 10.1111/ctr.14464
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant vaccination compliance in adult heart and lung transplant recipients

Abstract: Background: Vaccine preventable diseases can affect solid organ transplant recipients post-transplant. Therefore, the administration of vaccines and assessment of serologic response should be prioritized in the pre-transplant period.Methods: This single-center, retrospective study included 349 adult heart or lung transplant candidates between December 1, 2017 and November 30, 2019. We describe vaccination or serologic status for hepatitis A, hepatitis B, tetanus, pneumococcal, influenza, and other recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several interventions have been used to close the care coordination gap. Multiple studies have shown that transplant infectious diseases consultation in the pretransplant period is associated with higher rates of vaccination and seroresponse, compared with candidates who do not meet with an infectious diseases specialist [30 ▪ ,31 ▪ ]. These consultations may be most effective when linked to universal screening and vaccination protocols.…”
Section: Soft Stopsmentioning
confidence: 99%
“…Several interventions have been used to close the care coordination gap. Multiple studies have shown that transplant infectious diseases consultation in the pretransplant period is associated with higher rates of vaccination and seroresponse, compared with candidates who do not meet with an infectious diseases specialist [30 ▪ ,31 ▪ ]. These consultations may be most effective when linked to universal screening and vaccination protocols.…”
Section: Soft Stopsmentioning
confidence: 99%